Efficient terrain generation for game applications - Tjiong, Edwin Lesmana. (2009)
Modeling 3D terrain is subject to many applications, ranging from video game, flight simulation, building construction, geographical studies, etc. A lot of software has been released to support developers to create 3D terrain. However, many of these software are only used for their own fields and are not reusable in other applications.